2009
DOI: 10.1111/j.1532-849x.2008.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Dental Implants in Osteoporotic Patients. A Literature Review

Abstract: There are no data to contraindicate the use of dental implants in osteoporotic patients; however, a proper adjustment of the surgical technique and a longer healing period may be considered in order to achieve osseointegration. Data on the use of biphosphonates in osteoporotic patients and implant outcomes are very limited, and no conclusions can be drawn. In addition, large prospective studies investigating the long-term success of dental implants in osteoporotic individuals are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 131 publications
(241 reference statements)
0
62
0
4
Order By: Relevance
“…Thus, bone density at the implant placement site appears to be a crucial factor that is correlated with failure rate and primary stability (4,5). In fact, osteoporosis patients who undergo implant treatment have a less favorable outcome than patients with healthy bone (6). The most common secondary form of osteoporosis is that induced by glucocorticoid treatment for a great variety of inflammatory and allergic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, bone density at the implant placement site appears to be a crucial factor that is correlated with failure rate and primary stability (4,5). In fact, osteoporosis patients who undergo implant treatment have a less favorable outcome than patients with healthy bone (6). The most common secondary form of osteoporosis is that induced by glucocorticoid treatment for a great variety of inflammatory and allergic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Torque resistant to the cutting of bone during surgical preparation of implant site has also been used to present local bone quality and/ or indicate primary implant stability; obviously, IT also depends on other factors, such as implant geometry, threat from surface morphology, cutting tool design, and efficiency. [4][5][6][7][8][9] There is evidence to show that IT is related to local bone density. In a cadaver study, the peak IT of 24 selftapping screw-shaped implants was significantly correlated to the bone density calculated from CT. Another study involving 56 implants placed in 13 patients showed a correlation between IT of self-tapping screw-shaped implants and HUs.…”
Section: Introductionmentioning
confidence: 99%
“…Yayımlanan insan çalıĢmalarının sadece birinde sağlıklı ve osteoporozlu hasta grubunda osteointegrasyon açısından istatistiksel olarak anlamlı bir fark bulunmuĢtur. Ayrıca altı vaka raporu baĢarılı sonuçlar bildirirken sadece iki vaka raporunda osteointegrasyonda baĢarısızlık bildirilmiĢtir 47 . Bir baĢka önemli konu da hastalığın tedavisinde kullanılan bifosfonat terapisi altında bulunan bireylerde dental implant uygulamalarıdır.…”
Section: Osteoporozlu Hastalarda Dental İmplant Uygulamalarıunclassified
“…Bu grup ilaçların, kemiğe yüksek affinitelerinden ve yarılanma ömürlerinin yıllar ile ifade edilecek kadar uzun olmasından dolayı osteoklastik aktivite uzun dönemde etkilenmekte, gerek osteointegrasyon gerekse de osteointegrasyon sonrası periimplanter kemik yapım-yıkım (remodeling) dönemlerinde negatif etkisi bulunmaktadır. Bazı araĢ-tırıcılar, bifosfonat grubu ilaç tedavisi alan osteoporoz hastalarında dental implantların kesin kontraendikasyonu olduğunu vurgulamıĢlardır 47 . Ancak yapılan uzun dönem prospektif çalıĢmalarda, özellikle oral yolla kullanılan ve henüz tedavinin ilk üç yılında bulunan hasta grubunda uygulanan dental implantların baĢarısı, sağlıklı bireylere uygulanan dental implantların baĢarı-sından farklı bulunmamıĢtır 47 .…”
Section: Osteoporozlu Hastalarda Dental İmplant Uygulamalarıunclassified
See 1 more Smart Citation